New Queer Histories: Laura Doan's Disturbing Practices and the Constance Maynard Archive. Issue 1 (2nd January 2016) - Richardson, Elsa
Abstract : This review of Laura Doan's most recent work, Disturbing Practices: history, sexuality, and women's experience of modern war (2013) considers how this text might inform future readings of the Constance Maynard Archive. The work outlines a new methodological approach—'queer critical history'—to the history of sexuality. Carefully attuned to the overlapping taxonomical, linguistic, legal, medical and cultural agendas that contribute to the formation of sexual identities, this methodology allows the historian to reflect upon what remains unknowable about the sexual lives of the past, and to think more usefully about archival inconsistencies and silences.